Tuhfah Al-Qari’ Karya Abdul Qadir Al-Mandili: Pilar Hadis dalam Dakwah dan Psikologi Pendidikan - Pulungan, Nur Hamidah; Hayati, Nelmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The book Tuhfah al-Qari by Abdul Qadir is one of the essential sources in the study of hadith, contributing significantly to the fields of da'wah and Islamic education. In the modern era, many preachers seldom use hadith as the foundation for conveying Islamic teachings, which at times diminishes the authoritative strength of their da'wah messages. This study aims to analyze the relevance of Tuhfah as a reference for hadith-based da'wah and its connection to educational psychology. The research employs a qualitative-descriptive method with a library research approach. Data were collected from Tuhfah al-Qari and various relevant literatures on hadith, da'wah, and educational psychology. The findings indicate that this book provides a systematic arrangement of hadith that can enhance da'wah while emphasizing a psychological approach in delivering Islamic teachings. Therefore, this book serves as a strategic reference in developing more effective da'wah methods that align with the characteristics of the audience